The Right to Primary Healthcare in MERCOSUL: the Fraternity as a Possibility of Social Rights Guarantee - Martini, Sandra Regina; Barros Bellini, Maria Isabel (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2019)
This article discusses health as a fundamental and universal right therefore not limited to border demarcation, races and / or any other indicator . The analysis Locus is MERCOSUL- international organization between Brazil, Argentina , Paraguay and Uruguay established in 1991 to facilitate the integration of economic policies between these countries, it is associated with Chile and Bolivia. Discusses the importance of resizing the limits of law in today's society , for which the "frontier" is at the same time limits and possibilities between these to promote access to primary care as a bridge to the execution of other social rights thus breaking with traditional dimensions of the border or transfrontier idea where the right ended at the dividing line between one country and another.